2017
DOI: 10.18632/oncotarget.23152
|View full text |Cite
|
Sign up to set email alerts
|

Targeting dual specificity protein kinase TTK attenuates tumorigenesis of glioblastoma

Abstract: Accumulating evidence has proved that glioma stem-like cells (GSCs) are responsible for tumorigenesis, treatment resistance, and subsequent tumor recurrence in glioblastoma (GBM). In this study, we identified dual specificity protein kinase TTK (TTK) as the most up-regulated and differentially expressed kinase encoding genes in GSCs. Functionally, TTK was essential for in vitro clonogenicity and in vivo tumor propagation in GSCs. Clinically, TTK expression was highly enriched in GBM, moreover, was inversely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 28 publications
(35 reference statements)
3
54
0
Order By: Relevance
“…In glioma stem-like cells (GSCs), the MTFR2-dependent regulation of TTK was validated for a crucial role in maintaining GSCs in gliomas [44]. High expression of MCM2 in clinical samples was reported with CSC marker-positive breast cancer cells, and the MCM2-targeted therapeutic strategy, together with Hph-1-gp70 treatment to induce DNA damage, were regarded as a potential therapy for the eradication of stem-like cells from breast cancer tissue [45].…”
Section: Discussionmentioning
confidence: 99%
“…In glioma stem-like cells (GSCs), the MTFR2-dependent regulation of TTK was validated for a crucial role in maintaining GSCs in gliomas [44]. High expression of MCM2 in clinical samples was reported with CSC marker-positive breast cancer cells, and the MCM2-targeted therapeutic strategy, together with Hph-1-gp70 treatment to induce DNA damage, were regarded as a potential therapy for the eradication of stem-like cells from breast cancer tissue [45].…”
Section: Discussionmentioning
confidence: 99%
“…TTK has been identified as one of the promising candidates for vaccination in esophageal cancer patients with advanced stage disease 33,34 . Role of TTK in survival of cancer cells and cytotoxicity of its inhibitors has also been demonstrated in hepatocellular carcinoma 35 and glioblastoma 36 .…”
Section: Discussionmentioning
confidence: 95%
“…e proteins encoded by genes BUB1, BUB1B, and TTK have the ability to phosphorylate serine and threonine residues in the substrates [14], while TTK can also phosphorylate tyrosine residues, acting on checkpoints during cell mitosis [15]. It has been found that numerous tumors, such as glioblastoma [16,17] and gastric adenocarcinoma [18], harbor expression changes in BUB1, BUB1B, and TTK as well as checkpoint dysfunction. Moreover, BUB1, BUB1B, and TTK were shown to be associated with malignant behaviors such as PCPG metastasis in TCGAbased studies [19,20].…”
Section: Discussionmentioning
confidence: 99%